Além do musicoterapeuta: um estudo sobre a identidade do Musicoterapeuta e seu reconhecimento, fundamentado no sintagma identidade-metamorfose-emancipação - Godoy, Diego Azevedo (2015)
This research is intended to contribute to the study of metamorphosis processes and emancipatory movements, we seek to understand the formation and the development of professional identity of the music therapist, what are the possible dialectical movements of regulation / emancipation and the relations of recognition of professional identity, using the concept of identity developed by the theory of Ciampa (2007) and the theoretical assumptions of the nucleus of Study and Research in Identity Metamorphosis (NEPIM). Appropriating fundamentally of the conception of the syntagma: Identity-Metamorphosis-Emancipation, to develop a theoretical analysis of semi-structured interview of the subject based on the methodological foundation of the life history narrative. Since the main aspect of identity to be thorough in this research is in the dimension of recognition, we intend to study the relationship that the recognition of professional identity has with the recognition of personal identity, exploring collective identity and individual identity issues based in concepts such as: generalized other in Mead (1973), paper identity, identity of self in Habermas (1983), identity politics and political identities in Goffman (1975) / Ciampa (2002), and legal recognition and social esteem in Honneth (2003). After exposure of the literature review, the deepening on the assumptions of identity theory, and the methodological analysis of the interview, it is intended with the final considerations present data completed on the relationship that the recognition order occupies in the identity of the music therapist and the meaning attributed the same to relate their personal identity and their professional identity